Hybrid Finite Element And Monte Carlo Analysis Of Cracked Pipe - Mohd Akramin, Mohd Romlay; Amirruddin, Abdul Kadir; Nasrul Azuan, Alang (2010)
This paper presents a hybrid finite element and Monte Carlo analysis for fracture mechanics analysis of cracked structures. Probabilistic aspect is the main focus which related the nature of crack in material. The methodology involves finite element analysis; statistical models for uncertainty in material properties, crack size, fracture toughness and loads; and standard reliability methods for evaluating probabilistic characteristics of fracture parameter. Hybrid finite element and Monte Carlo analysis can provide the failure probability knowing that there is a crack and that the load can reach accidental values defined in a particular range. The probability of failure caused by uncertainties related to loads and material properties of the structure is estimated using Monte Carlo simulation technique. Therefore the proceeding either to repair the structure or it can be justified that an accident will not occur can be decided. Numerical examples are presented to show that probabilistic methodology based on Monte Carlo simulation provides accurate estimates of failure probability for use in fracture mechanics.